2005
DOI: 10.1086/429589
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Candidate Hirschsprung Disease–Associated RET Variants

Abstract: Patients with sporadic Hirschsprung disease (HSCR) show increased allele sharing at markers in the 5' region of the RET locus, indicating the presence of a common ancestral RET mutation. In a previous study, we found a haplotype of six SNPs that was transmitted to 55.6% of our patients, whereas it was present in only 16.2% of the controls we used. Among the patients with that haplotype, 90.8% had it on both chromosomes, which led to a much higher risk of developing HSCR than when the haplotype occurred heteroz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 16 publications
2
37
1
Order By: Relevance
“…Recent studies have suggested that the HSCR-associated RET mutations may be enhancer mutations, located approximately in the middle of intron 1 (Burzynski et al 2005;Emison et al 2005). Our previous study was consistent with this hypothesis.…”
Section: Introductionsupporting
confidence: 90%
See 2 more Smart Citations
“…Recent studies have suggested that the HSCR-associated RET mutations may be enhancer mutations, located approximately in the middle of intron 1 (Burzynski et al 2005;Emison et al 2005). Our previous study was consistent with this hypothesis.…”
Section: Introductionsupporting
confidence: 90%
“…This high risk may be related to features of their structures: both are located in conserved regions that contain binding sites for relevant transcription factors. Interestingly, rs1864410 is recognized by ubiquitous transcription factors, such as SP1-erk1(1) and AP2/SP1 (Burzynski et al 2005). These data suggest that rs1864410 and rs752975 may function as candidate disease-associated variants.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Several groups have characterized candidate diseaseassociated polymorphisms [49,[55][56][57]. Two promoter SNPs, rs10900296 and rs10900297 (also named SNP-5G > A and SNP-1A > C, respectively), located just upstream of the RET transcriptional start site, have been shown to reduce RET promoter activity in luciferase reporter assays [49,55], although others have shown that this effect is dependent on the cell lines studied [57].…”
Section: Hirschsprung Diseasementioning
confidence: 99%
“…Two groups have described two closely located SNPs, rs2435357 and rs2506004, in intron 1 as disease-causing candidates on the basis of association studies, functional assays and comparative genomics [52,56]. In particular, the last approach seems to be useful for judging the functional relevance of noncoding mutations, because it shows that the two disease-causing candidates are located in regulatory binding sites, which in turn are in regions that are conserved among different vertebrate species.…”
Section: Hirschsprung Diseasementioning
confidence: 99%